Qur'anic Education on Social Ethics - Basri; Jufri, Nurhikmah Itsnaini (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
This study aims to describe the content of verses from the Qur'an that provide education about how ethics are in undergoing association between fellow humans. Using descriptive-analytical methods, this study describes and analyzes the content of verses from the Qur'an about friendship or ethics in associations as well as several hadiths related to these verses. The results of this study show that friends or companions play an important role in a person's life. Bad effects may befall someone as a result of hanging out with friends who have a bad character. Vice versa, great benefits will also be obtained when getting along with good (pious) people. Therefore, the Qur'an has provided education on how ethics are in living relationships between fellow human beings. Namely: 1.) In associating, social interaction relationships between fellow human beings are established; 2.) In getting along there is a strong ukhuwwah bond. Namely by always being tolerant between religious people, avoiding all kinds of attitudes that can damage the relationship between mankind, always helping each other in kindness and avoiding hostility regardless of social background, and always having an airy attitude and being happy to forgive others; 3.) The establishment of a solid friendship in getting along.